Fairy Tale and Film - Short, S. author. aut Link
IX, 218 p.
Keywords: Sue Short examines how fairy tale tropes have been reworked in contemporary film, identifying familiar themes in a range of genres – including rom coms, crime films and horror – and noting key similarities and differences between the source narratives and their offspring.